(untitled) - Schultz, Duane P. (Orlando, Florida, 1996)
The book presents a history of modern psychology, not of psychology and all the philosophical work that preceded it. The book recounts the history of psychology in terms of its great ideas and schools of thought. Each of schools of thought is discussed as a movement growing out of its historical context and not only the intellectual spirit of the times but also social, political, and economic factors
Keywords: Behaviorism (Psychology),Cognitive psychology,Funtionalism (Psychology),Gestalt psychology,Humanistic psychology,Psychoanalysis,Psychology